The Cruciality of Self-Determination on James Baldwin’s Bruce and the Spider - Pasopati, Rommel Utungga; Noviyanti, Anisa Dinda; Wijaya, Kusuma; Kartiningsih, Rindrah; Hariyono (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This paper exposes the crucial points of self-determination in the flash fiction of James Baldwin entitled Bruce and the Spider. The short story is a narrative that describes a brief moment in the life of the main character, Bruce, a Scottish king who was defeated many times by the King of England. When he saw a spider weaving its web in the corner of his retreat, this moment became symbolic of Bruce's emotional journey and self-determination within himself and the kingdom of Scotland. In this flash fiction, it is witnessed how Bruce struggles amid his repeated failures. Using qualitative research method, this article illustrates small changes in perception and courage and asks questions about how simple moments can have a profound impact on a person's life. This writing is supported by Self-Determination Theory as conceptualized by Richard M. Ryan and Edward L. Deci. Through explorative approach, the analysis includes how self-determination accompanies the reflections of the meanings behind simple actions and the importance of facing failure. In conclusion, it is self-determination through self-confidence, self-understanding, and self-reliance that directs King Bruce to defeat his despair, get back up, and beat back the English soldiers.